Mechanism of injury and management in traumatic anterior shoulder dislocation with concomitant humeral shaft and ipsilateral scapula fracture: a case report and review of the literature - Farooque, Kamran (J Med Case Rep, 2014)
INTRODUCTION: Traumatic anterior dislocation of the shoulder is an emergency and warrants urgent attention. However, it becomes difficult to manage in cases of associated fractures of humerus and other bones surrounding the shoulder joint. There have been reports of traumatic anterior dislocation of the shoulder associated with humeral fractures in the literature but the trilogy of anterior dislocation of the shoulder; humeral shaft fracture; and scapular fracture have never been described. CASE PRESENTATION: We present the case of a 27-year-old south Asian man presenting with the above-mentioned injury. He was managed with open reduction and internal fixation of the fracture and subsequent reduction at the shoulder joint. The fracture of the scapula was managed conservatively. Radiological union was achieved at 14 weeks with a good range of movements at the shoulder. CONCLUSIONS: Shoulder dislocation associated with fractures of humerus and scapula occurs in rare circumstances due the peculiar mechanism of injury. There is risk of neurovascular damage while attempting joint reduction without fracture fixation so, in these cases, the fracture should be addressed first and dislocation later.